DIDACTIC AND ORIENTAL EDUCATION TENDENCIES (Conferencea, 2024)
The article discusses the relationship between oriental education and didacticism, the tendency relations between them, and theoretically analyzes the purely educational features based on value. The originality of the educational image found in the didactic works of Eastern, especially Uzbek literature, its role and importance in the development of a well-rounded person are highlighted.